Cardanol derived benzoxazine in combination with boron-doped graphene toward simultaneously improved toughening and flame retardant epoxy composites. (January 2019) - Guo, Wenwen; Wang, Xin; Gangireddy, Chandra Sekhar Reddy; Wang, Junling; Pan, Ying; Xing, Weiyi; Song, Lei; Hu, Yuan
Abstract: A bio-based phosphorus-containing benzoxazine monomer (CBz) was successfully synthesized through the reaction between cardanol and DOPO-based diamine. In order to simultaneously improve the toughness and flame retardancy of epoxy resin (EP), various contents of CBz in combination with boron-doped graphene (BG) nanosheets were incorporated into EP to obtain boron-doped graphene/cardanol derived benzoxazine-epoxy composites (EP/CBz/BG). By comparison, cardanol derived benzoxazine-epoxy co-polymers (EP/CBz) were also fabricated. Results show that the addition of the as-prepared CBz into EP not only endowed EP with excellent flame retardancy, but also improved the glass transition temperature and impact strength. Specifically, the peak heat release rate of EP composite with 13 wt% CBz and 2 wt% BG decreased by 48% compared to that of neat EP, accompanying with an increase of impact strength by 22%. These favorable features of EP/CBz/BG composites are attributed to the unique structure of CBz and high resistance to thermal decomposition of BG.